2020
DOI: 10.3389/fphar.2020.00505
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Plasma Protein Binding Characteristics and Unbound Concentration of Voriconazole on Its Adverse Drug Reactions

Abstract: This study investigated voriconazole (VRC) unbound plasma concentration and its relationship with adverse drug reactions (ADRs) in patients with malignant hematologic disease. Plasma samples were collected from patients or spiked in vitro. A time-saving rapid equilibrium dialysis assay was used for the separation of unbound and bound VRC, following a high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) analysis method for drug concentration detection. Liver function and treatment detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Kang et al found that ALT is a significant factor affecting VRZ concentration, in agreement with our results [32]. Although there is substantial evidence linking AST and VRZ concentration, we found no significant effect of AST in our model [33][34][35]. There are possible explanations for this.…”
Section: Discussionsupporting
confidence: 91%
“…Kang et al found that ALT is a significant factor affecting VRZ concentration, in agreement with our results [32]. Although there is substantial evidence linking AST and VRZ concentration, we found no significant effect of AST in our model [33][34][35]. There are possible explanations for this.…”
Section: Discussionsupporting
confidence: 91%
“…Here, there was still inter-individual variability in VRC concentrations and hepatotoxicity even among patients of the same metabolic type. In the past 2 decades, studies on the effects of treatment-related gastrointestinal changes, protein-binding changes, drug-drug interactions and even food intake on voriconazole metabolism have been reported ( Purkins et al, 2003 ; Hope et al, 2013 ; Yuan et al, 2020 ). While it has been shown that these physiological characteristics affect individual differences in response to voriconazole, the influence of inflammatory responses ( eg., CRP, IL-6) in combination with these physiological characteristics on the course of disease has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma protein binding rate of the samples was investigated using rapid equilibrium dialysis method ( Waters et al, 2008 ; Jiang C. et al, 2019 ; Yuan et al, 2020 ). In brief, the unbound drugs (or references) were separated from plasma (human and rat) in a 96-well plate with a semipermeable membrane through which only unbound drug can permeate.…”
Section: Methodsmentioning
confidence: 99%